Effect of pollen-mediated oxidative stress on immediate hypersensitivity reactions and late-phase inflammation in allergic conjunctivitis - Bacsi, Attila (2005)
BACKGROUND: Allergic eye diseases are complex inflammatory conditions of the conjunctiva that are becoming increasingly prevalent and present an increasing economic burden because of direct and indirect health expenditures. OBJECTIVE: We sought to identify factors that may synergize with antigen-induced allergic inflammation and lead to allergic conjunctivitis. We used a murine model of allergic conjunctivitis to test the effect of oxidative stress generated by pollen oxidases using nicotinamide adenine dinucleotide (reduced) or nicotinamide adenine dinucleotide phosphate (reduced) (NAD[P]H) as an electron donor present in pollen grains. METHODS: Reactive oxygen species (ROS) generation by hydrated Ambrosia artemisiifolia pollen (short ragweed pollen; RWP) grains was determined by using 2′-7′-dihydro-dichlorofluorescein diacetate, nitroblue tetrazolium reduction, and Amplex Red assay. The RWP-induced changes in intracellular ROS levels were examined in A549 cells, human primary bronchial epithelial cells, and murine conjunctiva. RESULTS: Ragweed pollen grains contain NAD(P)H oxidase activity, which is diphenyleneiodonium-sensitive and quinacrine-sensitive and sodium azide-resistant. These NAD(P)H oxidases generate a superoxide anion that can be converted to H(2)O(2) by pollen grain–associated superoxide dismutase. These diffusible oxygen radicals from pollen grains increase intracellular ROS levels in cultured epithelial cells and murine conjunctiva. Similar phenomena were observed in sensitized and naive mice, indicating that the RWP-induced oxidative stress in conjunctival epithelium is independent of adaptive immunity. Inactivation of NAD(P)H oxidase activity in RWP decreases the immediate-type hypersensitivity and inflammatory cell infiltration into the conjunctiva. CONCLUSION: Our data suggest that ROS generated by NAD(P)H oxidases in pollen grains intensify immediate allergic reactions and recruitment of inflammatory cells in murine conjunctiva.